The Changing Relationship between Māori and Environmentalists in 1970s and 1980s New Zealand - Mills, Keri (History compass, 2009)
Throughout most of New Zealand history there has been little interaction between the Māori protest movement and the environmental movement. This began to change during the 1970s and early 1980s, when environmentalists and Māori worked together to protest over government mismanagement of culturally valuable areas. This period of co-operation was short lived, the relationship becoming more complicated and politically tense from the late 80s onwards. This paper briefly surveys the literature on the histories and interests of the New Zealand environmental movement and the Māori protest movement, and discusses the changing relationship in this light.